Vibration control method for a crawler-type combine harvester - Zhang, Xueliang (Emirates Journal of Food and Agriculture, 2018)
The traditional vibration control method for the crawler-type combine harvester based on experience is only a small piece of weight iron added to the main drive shaft of the cutter,and the mass of the weight iron is determined by the technician with experience, so the vibration control effect is not obvious. Therefore, a vibration control method for the new crawler-type combined harvester is put forward in this paper. The engine and cutting structure are the main sources of the crawler-type combine. According to the force analysis results of the cutting structure and the results of structural dynamics analysis, each acting force and moment of force are obtained, and the optimal combination scheme for calculating the position and mass of weight distribution is calculated to solve the cutting structure’s vibration of the crawler-type combine harvester. According to the vibration theory and modern design method, the vibration control of the crawler-type combine harvester engine is realized through the model analysis and the finite element calculation to establish the vibration damping model and design the parameters of the damping cushion. The experimental results show that the proposed method can effectively improve the vibration status of crawler-type combine harvesters, and the vibration level of harvesters is reduced by 50% to 80% in field operation.